MODERN BIG DATA ARCHITECTURES : A MULTI-AGENT SYSTEMS PERSPECTIVE - Ryżko, Dominik, author 635758 (Hoboken, New Jersey : John Wiley & Sons, Inc., 2020)
"This book describes modern concepts and architectures for big data processing and analytics. It shows how data sets are produced and how they can be utilized to bring value in various branches of industry and science. It elaborates on how to apply common computational models and state of the art architectures to accomplish these tasks. Each chapter provides practical examples while describing solutions, which are universal and generic enough to be applicable in a wide variety of use cases. What is unique to this work, is the joint analysis of big data and multi-agent systems, with respect to distributed, intelligent processing of very large data sets. It is argued that we have arrived at the point of convergence of the base concepts of agent, actor, micro-service etc. and we can take the best from both fields in order to build next generation of systems"--